A simple eccentric stirred tank mini‐bioreactor: Mixing characterization and mammalian cell culture experiments. Issue 4 (26th November 2012) - Bulnes‐Abundis, David; Carrillo‐Cocom, Leydi M.; Aráiz‐Hernández, Diana; García‐Ulloa, Alfonso; Granados‐Pastor, Marisa; Sánchez‐Arreola, Pamela B.; Murugappan, Gayathree; Alvarez, Mario M.
Abstract In industrial practice, stirred tank bioreactors are the most common mammalian cell culture platform. However, research and screening protocols at the laboratory scale (i.e., 5–100 mL) rely primarily on Petri dishes, culture bottles, or Erlenmeyer flasks. There is a clear need for simple—easy to assemble, easy to use, easy to clean—cell culture mini‐bioreactors for lab‐scale and/or screening applications. Here, we study the mixing performance and culture adequacy of a 30 mL eccentric stirred tank mini‐bioreactor. A detailed mixing characterization of the proposed bioreactor is presented. Laser induced fluorescence (LIF) experiments and computational fluid dynamics (CFD) computations are used to identify the operational conditions required for adequate mixing. Mammalian cell culture experiments were conducted with two different cell models. The specific growth rate and the maximum cell density of Chinese hamster ovary (CHO) cell cultures grown in the mini‐bioreactor were comparable to those observed for 6‐well culture plates, Erlenmeyer flasks, and 1 L fully instrumented bioreactors. Human hematopoietic stem cells were successfully expanded tenfold in suspension conditions using the eccentric mini‐bioreactor system. Our results demonstrate good mixing performance and suggest the practicality and adequacy of the proposed mini‐bioreactor. Biotechnol. Bioeng. 2013; 110: 1106–1118. © 2012 Wiley Periodicals, Inc.